2015
DOI: 10.1002/jib.215
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to create an innovative craft durum wheat beer with sourdough yeasts? A case study

Abstract: Craft beer is often produced as a non-filtered, unpasteurized and bottle re-fermented beer, whose production is aimed at maintaining original sensory characteristics. The intention of most micro-breweries is to meet these requirements in producing a high-quality beer. In Italy, as well as in Sardinia, the number of micro-breweries is increasing. In an attempt to make this product more original, new strains of Saccharomyces cerevisiae were selected. Sourdough yeasts were used as an alternative source of starter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Marongiu et al () found that many S. cerevisiae strains isolated from sourdoughs were able to efficiently ferment wort, and pilot‐scale fermentations produced beer of the same quality as that produced by a commercial brewing yeast culture. This result was confirmed by Mascia et al () and Mascia, Fadda, Kerabín, Dostálek, and Del Caro (), who also compared sourdough isolates with a commercial culture, in this case for wheat beer brewing. Beers fermented with the sourdough‐derived cultures were found to be equivalent to or better than a commercial brewing strain with regard to yield and flavour profile.…”
Section: Repurposing Of Yeasts From Different Food and Beveragessupporting
confidence: 64%
“…Marongiu et al () found that many S. cerevisiae strains isolated from sourdoughs were able to efficiently ferment wort, and pilot‐scale fermentations produced beer of the same quality as that produced by a commercial brewing yeast culture. This result was confirmed by Mascia et al () and Mascia, Fadda, Kerabín, Dostálek, and Del Caro (), who also compared sourdough isolates with a commercial culture, in this case for wheat beer brewing. Beers fermented with the sourdough‐derived cultures were found to be equivalent to or better than a commercial brewing strain with regard to yield and flavour profile.…”
Section: Repurposing Of Yeasts From Different Food and Beveragessupporting
confidence: 64%
“…The use of sourdough strains in wort fermentations has been demonstrated previously and this approach is consistent with a growing interest in the potential value of non‐conventional yeasts in brewing . For example, strains of S. cerevisiae that have been re‐purposed for brewing include the probiotic strain S. cerevisiae var S. boulardii , an Andean chicha strain , and Brazilian cachaça strains .…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have demonstrated that sourdough derived S. cerevisiae strains, and even sourdough itself, can be used as starter cultures to ferment brewer's wort . There is, however, no information on how different strains can be used to differentiate beers ‐ either beers in general, or farmhouse ales in particular.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, choice of the yeast strain to use in the brewing process is also crucial to achieve a product that is valued by consumers and that has the required distinctive features and lavors. Also, yeast strains isolated from fermented foods other than beer can produce distinctive fermentative aroma proiles in beer [23,24]. They can transform lavor precursors of the raw materials into more lavor-active compounds, which thus contribute to the inal aroma of the beer [13,25].…”
Section: Novel Starters For Novel Beermentioning
confidence: 99%